The function \( f(x)=x^{3}+7 \) is one-to-one. a. Find an equation for \( f^{-1} \), the inverse function. b. Verify that your equation is correct by showing that \( f\left(f^{-1}(x)\right)=x \) and \( f^{-1}(f(x))=x \).
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Extra Insights
To find the inverse function of \( f(x) = x^3 + 7 \), we begin by letting \( y = f(x) \). This gives us the equation: \[ y = x^3 + 7. \] Next, solve for \( x \): 1. Subtract 7 from both sides: \[ y - 7 = x^3. \] 2. Take the cube root: \[ x = \sqrt[3]{y - 7}. \] Now swap \( x \) and \( y \) to express the inverse function: \[ f^{-1}(x) = \sqrt[3]{x - 7}. \] Next, let's verify the correctness of our inverse function. 1. Verify \( f(f^{-1}(x)) = x \): Substitute \( f^{-1}(x) \) into \( f(x) \): \[ f(f^{-1}(x)) = f(\sqrt[3]{x - 7}) = (\sqrt[3]{x - 7})^3 + 7 = x - 7 + 7 = x. \] This confirms that \( f(f^{-1}(x)) = x \). 2. Verify \( f^{-1}(f(x)) = x \): Substitute \( f(x) \) into \( f^{-1}(x) \): \[ f^{-1}(f(x)) = f^{-1}(x^3 + 7) = \sqrt[3]{(x^3 + 7) - 7} = \sqrt[3]{x^3} = x. \] Both verifications confirm that the inverse function is correct: \( f^{-1}(x) = \sqrt[3]{x - 7}. \)